Landscape composition mediates the relationship between predator body size and pest control. Issue 6 (10th June 2021) - Perez‐Alvarez, Ricardo; Grab, Heather; Polyakov, Anthony; Poveda, Katja
Abstract: Understanding the mechanisms contributing to positive relationships between predator diversity and natural pest control is fundamental to inform more effective management practices to support sustainable crop production. Predator body size can provide important insights to better understand and predict such predator‐pest interactions. Yet, most studies exploring the link between predator body size and pest control have been conducted in species‐poor communities under controlled environmental conditions, limiting our ability to generalize this relationship across heterogeneous landscapes. Using the community of naturally occurring ground beetles in cabbage fields, we examined how landscape composition (percent cropland) influences the size structure (mean, variance, and skewness of body size distribution) of predator communities and the subsequent effects on pest control. We found that predator communities shifted their size distribution toward larger body sizes in agriculturally dominated landscapes. This pattern arose from increasing numerical dominance of a few large‐bodied species rather than an aggregated response across the community. Such landscape‐driven changes in community size structure led to concomitant impacts on pest control, as the mean body size of predators was positively related to predation rates. Notably, the magnitude of pest control depended not only on the size of the dominant predators but was also strongly determined by the relative proportion of small vs. large‐bodied species (i.e., skewness). Predation rates were higher in predator assemblages with even representation of small and large‐bodied species relative to communities dominated by either large or small‐bodied predators. Landscape composition may therefore modulate the relationship between predator body size and pest control by influencing the body size distribution of co‐occurring species. Our study highlights the need to consider agricultural practices that not only boost effective predators, but also sustain a predator assemblage with a diverse set of traits to maximize overall pest control.